Simulation of mosul dam breaks using basement model - Basheer, Talal A. (2018)
Dams have been constructed for many purposes such as water supply, flood control, irrigation, and hydropower generation. They provide numerous benefits to civilization; however, floods resulting from a dam break could lead to tremendous loss of lives and properties. Mosul Dam, the largest dam in Iraq, is located in the northwestern part of the country. The problem of Mosul Dam is the continuous corrosion in the dam foundations that contain gypsum and anhydrite formations, which dissolve under the effect of storing water in the reservoir. According to the US Army Corps of Engineers 2006 report “in terms of internal erosion potential of the foundation, Mosul Dam is the most dangerous dam in the world”. The main objectives of this research were to predict the flood occurrence after the probable Mosul Dam break and develop maps of the downstream flooded areas to identify the zones under potential risk in Mosul city. Dam break studies depend on three primary tasks mainly; predicting the breach parameters, estimating the breach flood hydrograph and routing this hydrograph downstream of the dam site. In this study, five breach prediction approaches were implemented to predict the breach geometry and the required time for breach formation. In addition to that, overtopping and piping failure modes were considered. For each approach, eight reservoir water levels, ranging from minimum operation level to maximum storage level with 5 m intervals, were studied. Sensitivity analysis was carried out to evaluate the effect of breach parameters on the resulting flood hydrographs. The topography of the study area was demonstrated using a 30 m × 30 m Digital Elevation Model (DEM). In this study, the downstream flood propagation of the Mosul Dam break was simulated using the two-dimensional BASEMENT version 2.5.3 numerical model. The numerical model was utilized to the Tigris River between Mosul Dam and south of Mosul city along 87.8 km. The breach flood hydrographs for each scenario were analyzed and discussed. The results show that the overtopping failure mode tends to give higher peak discharge values than the piping failure mode by 1.8 to 19.6% in case of 330 and 300 m reservoir water levels, respectively. In addition, results indicate that the most suitable method for estimating breach parameters for large dams was the Froehlich (2008) approach. Furthermore, for large dams, such as Mosul dam, the sensitivity analysis shows that the breach side slope does not affect the peak discharge time and has a minor influence on peak outflow values. Meanwhile, the required time for the breach to develop was highly sensitive to both peak discharge and peak discharge time. For instance, increasing breach formation time by 50% led to decreasing peak discharge by 19.19% and shifted the peak discharge time from 6 hours to 9.5 hours. Based on the simulation results, indicative inundation maps for multiple scenarios have been presented in this study. The time lag between the start of the failure of Mosul dam and arrival of the peak flow to Mosul city for all cases were stated. In addition to that, the flood peak discharge, peak water level, and lag time of peak discharge along the Tigris River reach for various values of reservoir water level were specified and analyzed. A new empirical model relates the maximum wave depth along the main stream with the initial condition of the reservoir and the breach dimension has been developed. This new empirical model is highly significant in estimating the maximum flood depth as compared to the simulation results using BASEMENT model.